Gambaran Motivasi Anggota Mengikuti Koperasi Jasa Keuangan Syariah Baitul Maal Wat Tamwil (KJKS- BMT) - Witrawatis, Witrawatis; Setiawati, Setiawati (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This research is motivated by the many people who have joined as members of the Baitul Maal Wat Tamwil Sharia Financial Services Cooperative (KJKS-BMT). This is allegedly the high motivation of the community. This study aims to see the picture (1) intrinsic motivation of cooperative members, (2) extrinsic motivation of cooperative members. This type of research is quantitative descriptive with the population of 160 cooperative members. The sample of this research is 40 people. The sampling technique is done randomly (random sampling). Data collection techniques using a questionnaire (questionnaire) and data analysis techniques using the percentage formula. The results showed that (1) the intrinsic motivation of members following cooperatives was categorized high (2) the extrinsic motivation of members following cooperatives was categorized high. Based on the results of the study it is recommended that intrinsic motivation and extrinsic motivation of members in participating in programs in cooperatives be further enhanced so that activities in cooperatives lead to the expected success.